Correspondence from Stephen L. Joyner to Dr. D. Robert Howard regarding funding for attendance at the North Carolina Medical Society Annual Meeting (1970 : Pinehurst, N.C.). - Joyner, Stephen L. (1970)
Letter from Stephen Joyner, AAPA Board of Directors, to D. Robert Howard, Director of the Duke University PA program, thanking him for considering financial support for him and Dick Scheele [correct spelling Scheele] to attend and display at the North Carolina Medical Society Annual Meeting, May 1970 at Pinehurst, N.C.